Effect of zirconium oxide local structure on soft x-ray optical properties near the oxygen K-edge region - Sinha, Mangalika; Gupta, Rajkumar; Kiranjot; Singh, Amol; Modi, Mohammed H. (Journal of applied physics, 2020)
Zirconium oxide thin film serves as one of the potential material candidates in extreme ultraviolet/soft x-ray optics applications. The suitability of its application can be justified by investigating its optical performance in the working energy range. In this study, we have investigated the soft x-ray optical properties of a zirconium oxide thin film near the O K-edge region using the energy-dependent soft x-ray reflectivity (SXR) technique. The SXR and absorption measurements are performed using the Indus-2 soft x-ray reflectivity beamline BL-03. The optical constants (δ and β) in the energy range of 500–560 eV covering O K-edge are extracted by applying Kramers–Kronig relations. Experimentally obtained δ and β profiles show a prominent eg and t2g feature in the vicinity of O K-edge with the crystal field splitting of 2.9 eV. All features observed in the δ and β spectra are correlated with their electronic structure and composition of the zirconium oxide thin film. Details of correlation between structural and optical properties as determined by x-ray absorption spectroscopy, x-ray photoelectron spectroscopy, and SXR analyses are discussed.